Chaperone Hsp31 Contributes to Acid Resistance in Stationary-Phase Escherichia coli - Mujacic, Mirna (American Society for Microbiology, 2007)
Hsp31, the product of the σ(S)- and σ(D)-dependent hchA gene, is a heat-inducible chaperone implicated in the management of protein misfolding at high temperatures. We show here that Hsp31 plays an important role in the acid resistance of starved Escherichia coli but that it has little influence on oxidative-stress survival.